Optimization of truck-loader haulage systems in an underground mine using simulation methods. Issue 5 (2nd September 2016) - Park, Sebeom; Choi, Yosoon; Park, Han-su
Abstract: This study developed a program to simulate a haulage system with trucks and loaders for an underground mine using the GPSS/H simulation language. The Daesung MDI limestone mine located in Korea was selected as the study area. Using the developed program and parameter values determined by a field survey, simulations of the truck-loader haulage system were performed to optimize the number of trucks dispatched at three loading points in the study area. The simulation results showed that maximum production can be expected by dispatching four, seven, and three trucks to each loading point, respectively. Because the developed program was found to properly simulate the haulage system, it could be used for practical purposes in the study area.